2007
DOI: 10.1073/pnas.0608050104
|View full text |Cite
|
Sign up to set email alerts
|

The species, sex, and stage specificity of a Caenorhabditis sex pheromone

Abstract: Four species in the ELEGANS group of the subgenus Caenorhabditis are distinguished by two very different mating systems: androdioecy in C. elegans and Caenorhabditis briggsae with males and self-fertilizing hermaphrodites and dioecy in Caenorhabditis remanei and Caenorhabditis sp. strain CB5161 with males and females. Using chemotaxis assays, we demonstrate that females secrete a potent sex pheromone that attracts males from a distance, whereas hermaphrodites do not. The female sex pheromone is not species-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
184
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(193 citation statements)
references
References 17 publications
7
184
0
Order By: Relevance
“…Chasnov et al (7) showed that females of C. brenneri and C. remanei produce an unknown volatile pheromone only if they have not recently been inseminated by conspecific males. C. elegans hermaphrodites produce no such pheromone; however, hermaphrodites of C. elegans reach adulthood already containing enough sperm to last nearly 3 d (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chasnov et al (7) showed that females of C. brenneri and C. remanei produce an unknown volatile pheromone only if they have not recently been inseminated by conspecific males. C. elegans hermaphrodites produce no such pheromone; however, hermaphrodites of C. elegans reach adulthood already containing enough sperm to last nearly 3 d (17).…”
Section: Resultsmentioning
confidence: 99%
“…Mutant C. elegans hermaphrodites that develop without self-sperm also elicit more mating attempts, and this increase in attractiveness vanishes after a successful mating (5,6). In the gonochoristic species Caenorhabditis brenneri and Caenorhabditis remanei, males are attracted to a volatile pheromone produced only by females that have not recently mated (7). The mechanisms that link these behaviors to sperm status remain unknown.…”
mentioning
confidence: 99%
“…First, a long-range pheromone acts to attract males (Chasnov et al, 2007). Next, a short-range and short-lived hermaphrodite signal triggers male searching behavior (Lipton et al, 2004).…”
Section: Elegans Male Sexual Behavior and The Turning Step Of Malementioning
confidence: 99%
“…In C. elegans, male-specific sexual behavior consists of copulation and exploratory behavior (Lipton et al 2004;Barr and Garcia 2006;Emmons 2006). Exploratory behavior serves to bring males into the vicinity of hermaphrodite mates, where they respond to short-range secreted cues (Simon and Sternberg 2002;Chasnov et al 2007;White et al 2007). During copulation, the male slides its tail along the hermaphrodite body to find the vulva, inserts its spicules, and transfers sperm.…”
mentioning
confidence: 99%